Usage and Impact of Teachers Self-Assessment Practices on Teaching of Upper Basic Social Studies in Kwara State - Olokooba Isaa Nasiru; Elizabeth Obiageli Uyanne (Universitas Ahmad Dahlan, 2022)
Background: Self-assessment is a mechanism that enables teachers to reflect how their own work meets the goals. It is set for teaching concepts and enhancing effective teaching and learning. The objectives of this study are to investigate prevalent patterns of self-assessment practices, extent of using as well as the impacts of self-assessment practices on teaching Social Studies. Contribution: This study investigates impact of teachers’ self-assessment practices on teaching of upper basic Social Studies. Method: Through simple random sampling technique, 600 upper basic Social Studies teachers were selected. A questionnaire is used for data collection. Percentage and mean ranking were used to analyze the collected data. Results: The findings of the study show that peer observation, testing the flexibility of teaching style and activity reports are prevalent patterns of self-assessment practices and frequently used. The practices have impacts on teaching of upper basic Social Studies in schools. Conclusion: it is recommended that teachers should constantly self-assess their teaching processes to recognize and improve on the progress teaching in the classrooms.